The effects of habitat type and pathogen infection on tick host-seeking behaviour. Issue 1 (6th January 2022) - Richardson, Elise A.; Taylor, Caitlin E.; Jabot, Brittney; Martin, Estelle; Keiser, Carl N.
Abstract: Abstract: Tick-borne pathogens pose a significant risk to livestock, wildlife and public health. Host-seeking behaviours may depend on a combination of infection status and environmental factors. Here, we assessed the effects of habitat type and pathogen infection on host-seeking behaviour (questing) in the lone star tick, Amblyomma americanum . Ticks were collected using a tick drag from two different habitat types: xeric hammock and successional hardwood forests. Using a standardized assay, we recorded the likelihood of questing for each tick, the average height quested and total time spent questing and then tested each tick for the presence of Rickettsia spp. and Ehrlichia spp. using conventional polymerase chain reaction. We did not detect Ehrlichia in any ticks, although 30% tested positive for Rickettsia amblyommatis, a member of the Rickettsia spotted fever group. Ticks infected with R. amblyommatis spent less time questing compared to uninfected ticks, with infected ticks spending 85 s on average questing and uninfected ticks spending 112 s. Additionally, ticks collected from xeric hammock habitats spent over twice as long questing compared to ticks from successional hardwood forests. Ticks from xeric hammock spent 151 s on average questing while ticks from successional hardwood forest spent only 58 s during a 10-min observation period. These results demonstrate that habitat type and infection status can influence tick host-seeking behaviours, which can play a pivotal role in disease dynamics.